Endoscopy‐assisted breast‐conserving surgery for early breast cancer. Issue 3 (1st February 2013) - Saimura, Michiyo; Mitsuyama, Shoshu; Anan, Keisei; Koga, Kenichiro; Watanabe, Masato; Ono, Minoru; Toyoshima, Satoshi
Abstract Introduction Endoscopic surgery is reportedly associated with smaller scars and greater patient satisfaction. Herein we evaluate the early results of endoscopy‐assisted breast‐conserving surgery(E‐BCS). Methods Between May 2009 and October 2010, 61 women with breast cancer underwent E‐BCS. We performed E‐BCS on patients with tumors measuring less than 2 cm, without skin or pectoralis muscles invasion. Any patients with microcalcified lesions or axillary lymph node metastasis were excluded. We used an endoscopic vein retractor to dissect the dorsal layer of the mammary gland from a small axillar incision. We dissected the subcutaneous layer and cut the mammary gland vertically from a periareolar incision. We evaluated the clinicopathological characteristics, the surgical outcomes, and early cosmetic results. Results The mean age of the patients was 58.5 years, and the mean tumor size was 1.4 cm. Sentinel node biopsy was positive in seven patients, all of whom underwent axillary node dissection. An additional intraoperative resection of the breast was performed in 12 patients. The mean length of the operation was 167 min, and the mean blood loss was 27 mL. Eight patients received a boost to the tumor bed. The cosmetic results were satisfactory, and the wound scar was inconspicuous in most patients. Conclusion Herein we demonstrate that E‐BCS is a feasible and safe procedure for patients with early breast cancer. It allows for a better cosmetic scar location and offers patients favorable aesthetic results in the short‐term follow‐up results.